2019
DOI: 10.1007/s00414-019-02014-3
|View full text |Cite
|
Sign up to set email alerts
|

Helium poisoning: new procedure for sampling and analysis

Abstract: An increasing number of suicidal asphyxiation with a plastic bag with inert gases, and in particular helium (He), have been reported from numerous countries over the last decade. These cases are differently managed and lead to different and variable interpretations. Based on the twelve last cases analysed in the laboratory and on the review of the most recent literature about this topic, updated autopsy guidelines for sampling have been proposed regarding to the samples choice and analytical challenges require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…Tsujita et al [47] demonstrated that hydrogen gave the highest intensity and the good shape of helium peak as compared to argon or nitrogen as a mobile phase. It was also suggested and confirmed by Varlet et al [44] to use hydrogen as a carrier gas to obtain the best selectivity and sensitivity of the method. According to the available literature data, volatile substances are analyzed under isothermal conditions [3,10,20,36,37,[44][45][46][47].…”
Section: Methods Of Detecting Helium Poisoningsmentioning
confidence: 86%
See 4 more Smart Citations
“…Tsujita et al [47] demonstrated that hydrogen gave the highest intensity and the good shape of helium peak as compared to argon or nitrogen as a mobile phase. It was also suggested and confirmed by Varlet et al [44] to use hydrogen as a carrier gas to obtain the best selectivity and sensitivity of the method. According to the available literature data, volatile substances are analyzed under isothermal conditions [3,10,20,36,37,[44][45][46][47].…”
Section: Methods Of Detecting Helium Poisoningsmentioning
confidence: 86%
“…Due to the physical properties of helium (gas), the only methods enabling its separation are variants of gas chromatography (GC), e.g., GC with headspace analysis. The most commonly used detectors are mass spectrometers (MSs) [3,10,20,[44][45][46][47] and thermal conductivity detectors (TCDs) [36][37][38]48]. However, Tsujita et al [47] pointed out the poor selectivity and sensitivity for helium detection by GC-TCD.…”
Section: Methods Of Detecting Helium Poisoningsmentioning
confidence: 99%
See 3 more Smart Citations